Foods of Spain - Sheen, Barbara (New York Kidhaven Press, 2008)
This book explores the foods, cooking traditions, customs, eating habits, and food sources; all presented through a delectable blend of geography, daily life, culture, and history.
1 - 6
Keywords: 1. Cookery, Spanish; 2. Spain - Social life and customs; 3. A Taste of Culture